Posttraumatic Growth as a Model to Measure and Guide Implementation of COVID-19 Recovery and Resiliency. Issue 1 (January 2022) - Cunningham, Tim; Pfeiffer, Kate
Abstract : The COVID-19 pandemic has forced leaders to reconsider the various factors that attribute to work-life balance, a healthy work environment, and resilience among nurses. Posttraumatic growth (PTG) provides a lens through which clinicians and leaders can measure, articulate, and espouse resilient recovery through unprecedented times. This article suggests the use of PTG as a framework, measured by the Posttraumatic Growth Inventory to guide leaders as they implement job-specific resiliency interventions for professional nurses. This article also suggests 3 science-based interventions intended to increase PTG. Published data support the efficacy of these interventions: resilience retreats, resilience rounds, and "The Pause, " while longitudinal impacts of PTG following these interventions remain currently unknown.